Collective skill formation regimes in times of Covid-19 : a governance-focused analysis of the German dual training system - Faßbender, Uwe [Verfasser] (My University, 2022)
„Context: Covid-19 poses major challenges for vocational education and training (VET), as VET - in contrast to general education - is closely linked to the economic system and cannot escape the impact of current economic restrictions. Additionally, strict infection control regulations, as well as temporary school and company closures, inhibit the teaching of practical skills at the workplace. Rapid action by the responsible actors is essential to ensure that VET can take place even under these difficult conditions. It can be assumed that both the complex decision-making processes and the multiplicity of actors involved in collective training systems complicate or delay the reaction to this exogenous shock. Using the example of the German dual training system, this explorative article aims to examine the ability of collective training systems to deal with the challenges posed by the pandemic. Methods: Based on a document analysis, various publications (e.g., press releases, reports) by central actors of the German dual system were reviewed, which provided information about the provision of training activities as well as the measures taken or required to counteract the pandemic-related consequences for dual apprenticeships. This corpus of literature was expanded by scientific studies and publications from national or international institutions related to VET. Following a governance-analytical and actor-centred perspective, the documents were analysed with regard to the indications they provide about the realised coordination of action between the actors, the realised processes and outcomes, as well as the levels affected within the VET system. Findings: The way of dealing with the crisis demonstrates that the German dual system is influenced by the actions of various actors at multiple levels. Actors who are involved in the decision-making processes share common interests, resulting in a strategically bound cooperation among them. However, influence or power from bottom-up seems to be rather limited, as not all of the actors considered in this study are included in essential governance processes. Despite the comprehensive reactions to the pandemic, problems and optimisation needs are also apparent, e.g. with regard to vocational orientation or the support of vocational schools.“ (author’s abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; 370; Berufsausbildung; Pandemie; Auswirkung; Literaturanalyse; Governance